2022
DOI: 10.22603/ssrr.2021-0051
|View full text |Cite
|
Sign up to set email alerts
|

Brace-Related Stress and Quality-of-Life Parameters in Adolescents with Idiopathic Scoliosis

Abstract: Introduction:This study investigated brace-related stress, trunk appearance perception, and quality of life in adolescent girls with idiopathic scoliosis who wear the Milwaukee brace for treatment.Methods: Fifty-two adolescent girls with idiopathic scoliosis participated in this study. They had been under treatment with Milwaukee brace for at least three months. They filled out four questionnaires, including the revised 22-item Scoliosis Research Society questionnaire (SRS-22r), the Brace Questionnaire (BrQ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our results suggested that the QOL measured by QLPSD decreased with age. Similarly, a recent research showed that participants under the age of 13 had a superior self-image score on the SRS-22 than adolescents beyond the age of 13 [ 30 ]. The higher brace compliance in younger than in older teenagers may be a possible reason for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the QOL measured by QLPSD decreased with age. Similarly, a recent research showed that participants under the age of 13 had a superior self-image score on the SRS-22 than adolescents beyond the age of 13 [ 30 ]. The higher brace compliance in younger than in older teenagers may be a possible reason for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite often being asymptomatic and non-life-threatening, the resultant deformities of AIS can significantly affect patients' quality of life (QoL), 4 eliciting concerns about physical appearance, pain, and functional limitations. 1 The current management approach for AIS encompasses both surgical and conservative treatment. Conservative treatments include orthotic spinal bracing, exercise, and clinical monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Although many forms of scoliosis exist, most of the scoliosis cases (84%–89%) are reported in previously healthy teenagers during the adolescent growth spurt 3 . Despite often being asymptomatic and non‐life‐threatening, the resultant deformities of AIS can significantly affect patients' quality of life (QoL), 4 eliciting concerns about physical appearance, pain, and functional limitations 1 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations